Evaluation of pharmacokinetic/pharmacodynamic and clinical outcomes with 6-hourly empiric piperacillin-tazobactam dosing in hematological malignancy patients with febrile neutropenia. Issue 7 (July 2019) - Weber, Nicholas; Jackson, Kathryn; McWhinney, Brett; Ungerer, Jacobus; Kennedy, Glen; Lipman, Jeffrey; Roberts, Jason A.
Abstract: Background: Piperacillin-tazobactam is commonly used in neutropenic sepsis at standard doses that do not account for inter-individual differences in age, bodyweight and renal function. This study was designed to assess the rate of attainment of pharmacokinetic/pharmacodynamic (PK/PD) targets in patients receiving piperacillin/tazobactam therapy and to evaluate the effect on clinical outcomes. Methods: Patients undergoing intensive chemotherapy for aggressive hematological malignancies were enrolled and treated with piperacillin/tazobactam 4 g/0.5 g every 6 h as initial antimicrobial therapy for first fever. Plasma drug concentrations were assayed at 50% and 100% of the dosing interval and compared with target MIC breakpoint of 16 mg/L to calculate the primary endpoints of 50% and 100% time above MIC (fT > MIC), respectively. Secondary endpoints included time to clinical cure, length of hospital stay, duration of antibiotics, and clinical treatment success. Results: Fifty-eight percent (14/24) of patients achieved 50% fT > MIC while only 4% (1/24) achieved 100% fT > MIC. Higher creatinine clearance was significantly associated with lower trough drug concentration and appeared to be the dominant reason for the poor PK/PD target attainment. Median time to clinical cure, duration of antibiotic therapy, and hospital length of stay was 3, 13 and 21 days, respectively. There were no statistically significant differences in these outcomes between patients who did and did not achieve 100% fT > MIC. Conclusions: A significant majority of febrile neutropenic patients fail to achieve PK/PD targets with 6-hourly piperacillin dosing, although the clinical implications of this finding are unclear. Larger studies are needed to assess any impact on morbidity and mortality. This trial is registered on the ANZCTR (ACTRN12618000110280).